Dampak Kesesuaian Syariah dan Variabel Lainnya Terhadap Tingkat Underpricing pada Penawaran Saham Perdana di Indonesia - Rumanto, Agep (IAIN Kudus, 2022)
This study aims to analyze whether there is an effect of sharia compliance with the level of underpricing in Indonesia. In addition to sharia compliance factors, other factors are also included, namely firm size, stock offering, company age, underwriter reputation, risk factors, and market conditions. This study uses a range of IPO sample data between 2011 and 2015. The test results show that there is a simultaneous influence of the seven dependent variables, namely sharia compliance, company size, stock offering, company age, underwriter reputation, risk factors and market conditions on the level of underpricing. Only risk factors and underwriter reputation have a significant effect on the level of underpricing. While the sharia compliance factor itself which is the main hypothesis in this study has no effect on the level of underpricing in Indonesia.